Extending Mental Health Diagnostic Privileges to Social Workers in Saskatchewan - Stephanie E. Austin (McMaster University Library Press, 2017)
Bill 78, An Act to amend The Social Workers Act, was passed in 2013 in Saskatchewan, allowing social workers to diagnose mental health disorders. Social workers previously had diagnostic privileges until the Psychologists Act was passed in 2002. The goal of the reform is to reduce wait times to access mental health services and diagnoses. The reform was introduced following extensive lobbying by the Saskatchewan Association of Social Workers (SASW) and during a time of increased recognition of mental health issues both provincially and nationally. The reform will be implemented using regulatory instruments through the SASW and its by-laws, however the by-laws - updated to include provisions for Authorized Practice Endorsement, or in other words diagnosis of mental health disorders - have not, to date, been implemented. Accordingly, an evaluation of the reform has also not yet been conducted. Overall this reform is expected to improve access to mental health services, however concerns remain about availability of government funding and programs for treatment and services following diagnosis.